The Effect of Ladder Drill Exercise on Speed, Surrounding, and Power Leg Muscle - Kusuma, Ketut Chandra Adinata; Kardiawan, I Kadek Happy (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
This study aimed at finding the effect of ladder drill training upon: (1) run speed, (2) agility, and (2) power of leg muscle. This study is an experimental research. This study utilized one group pre test-post test design. There were total people as the subject of this research. Data collection technique used 30-meter sprint test to measure run speed, Illinois agility test to measure agility, and vertical jump test to measure power of leg muscle. Data analysis technique which was used for normality test, homogeneity test/F-test, and T-test with significant level 5% by using SPSS 16.0.0. Based on the finding, there was effect of ladder drill training upon run speed with sig value=0.007, agility and power of leg muscle with sig value=0.000. Based on the data analysis, it could be concluded that there was significant effect of ladder drill training upon run speed, agility and power of leg muscle.